Fight for liberty and freedom : the origins of Australian Aboriginal activism - Maynard, John, 1954- (Canberra : Aboriginal Studies Press, 2007)
The Australian Aboriginal Progressive Association (AAPA), begun in 1924, is little heard of today, but today's Aboriginal political movement is drawn from these roots. In this passionate exploration of the life of founder, Fred Maynard, John Maynard reveals the commitment and sacrifices made by these Aboriginal heroes. Decades earlier than is commonly understood, Aboriginal people organised street rallies and held well-publicised regional and metropolitan meetings. The AAPA showed incredible aptitude in using newspaper coverage, letter writing and petitions, and collaborated with the international black movement through Maynard's connections with Marcus Garvey, first president of the Universal Negro Improvement Association (UNIA). The AAPA's demands resonate today: Aboriginal rights to land, preventing Aboriginal children being taken from their families, and defending a distinct Aboriginal cultural identity.
Includes index.
Bibliography: p. 144-151.
Keywords: Maynard, Frederick, -- 1879-1946.; Australian Aboriginal Progressive Association; Aboriginal Australians -- Politics and government; Aboriginal Australians -- History -- 20th century; Political activists -- Australia; Aboriginal Australians -- Civil rights; Aboriginal Australians -- Legal status, laws, etc; Politics and Government - Political action - Activism; Child welfare - Child / parent separation - Stolen generations; Politics and Government - Civil rights and citizenship; Settlement and contacts - Resettlement and removals; Politics and Government - Political action - Non-Indigenous.; Government policy - State and territory - New South Wales; Kempsey (NSW N Coast SH56-14); Lismore (NSW N Coast SH56-03); Grafton (NSW N Coast SH56-06); Sydney (NSW SI56-05); La Perouse (S Sydney NSW SI56-05)